Pengaruh Promosi, Harga dan Kualitas Produk Terhadap Minat Beli Konsumen Kerudung Rabbani - Muhammad, Saikoo; Nugraha, Hari Susanta; Prabawani, Bulan (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2016)
This research is motivated growing fashion industry, one of fashion products are rising that the veil or hijab. From a business perspective, hijabers phenomenon has great potential in the fashion industry, especially in industrial veils. Manufacturers producing veil one of which was Rabbani who is a garment company and one of the first instant veil companies in Indonesia. Many manufacturers competitors like Zoya, Pashmina, and shasmira are also more aggressively promote its products. Rabbani has decreased the percentage of sales in 2011 to 2014This research aims to determined the effect of the Promotion, Price and Quality Products toward Interest Buy of the consumer of Rabbani’s Veil Dipatiukur Bandung. This type of research is explanatory research, data collection techniques are based interviews questionnaires, cluster sampling technique of sampling and the number of samples 120. Data were analyzed through validity test, reliability test, correlation coefficient, determination coefficient, simple linear regression, multiple linear regression, t test and F test data were analyzed quantitatively using SPSS.This study showed that promotion, price and product quality effect on consumer buying interest either partially or simultaneously. The quality of products provide greatest influence on the consumer buying interest Dipatiukur veil Rabbani Bandung.The conclusion promotions, price and higher quality products, the higher the purchase interest. Rabbani suggested further enhance the promotion of the use of language which clear and persuasive language, pricing according to segmentation, diversity of models and styles, and products provided should continue to follow the fashion trend.